2019
DOI: 10.1108/ijpsm-03-2018-0081
|View full text |Cite
|
Sign up to set email alerts
|

Key drivers for public value creation enhancing the adoption of electronic public services by citizens

Abstract: Purpose The relationship between citizens and government has been gradually changing from government centered to citizen centered. These changes can be understood from the public value perspective, which is a promising way to foster the use of electronic services (e-services) by citizens. The purpose of this paper is to analyze how key drivers for public value creation can enhance adopting electronic public services by citizens. The use of e-services as a basis for applying smart technologies is also discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
4
10
0
1
Order By: Relevance
“…[59] Innovation orientation [1], [11], [14], [45] Productivity [1], [11], [25] Satisfy users' needs [1], [11], [12], [17], [63], [68] Service enhancement [1], [4], [10]- [12], [14], [17], [19], [25], [37], [40], [50], [56], [69] Better management of public resources and funds [1], [11] Responsiveness [1], [4], [11], [12], [35], [50], [61], [67] Respect for the individual [1], [11], [63] 2. Improved Administrative Efficiency Accountability within public organization [1], [11], [17], [25], [51], [59] Cost reduction and savings [1], [11], [38] Competitiveness…”
Section: Public Value Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…[59] Innovation orientation [1], [11], [14], [45] Productivity [1], [11], [25] Satisfy users' needs [1], [11], [12], [17], [63], [68] Service enhancement [1], [4], [10]- [12], [14], [17], [19], [25], [37], [40], [50], [56], [69] Better management of public resources and funds [1], [11] Responsiveness [1], [4], [11], [12], [35], [50], [61], [67] Respect for the individual [1], [11], [63] 2. Improved Administrative Efficiency Accountability within public organization [1], [11], [17], [25], [51], [59] Cost reduction and savings [1], [11], [38] Competitiveness…”
Section: Public Value Dimensionmentioning
confidence: 99%
“…[59] Reliability [1], [11], [61] Process automation [1], [11] Errors reduction [1], [11] Process optimization sustainability [1], [11], [61], [67] Governance [1], [11], [56], [63] Better management of [1], [11]…”
Section: Public Value Dimensionmentioning
confidence: 99%
“…Their study revealed that security and satisfaction significantly influenced the intention to use an e-service and the acceptance of e-service technology in Malaysia. Lopes et al [8] found four main keys that could increase the adoption of electronic public services by citizens in Brazil: collaborative process, governmental readiness, E-service design, and citizen trust. In the context of developed countries, several factors such as trust of the Internet, trust of the government, perceived ease of use, perceived usefulness, and perceived risk are used as models to see the effect on the intention to use government e-services [9,12].…”
Section: Related Workmentioning
confidence: 99%
“…In general, the studies look at adoption factors from the technology dimension, such as perceived ease of use or performance expectancy and perceived usefulness or effort expectancy. Since these studies did not provide sufficient information to understand adoption behavior, several other studies also involved trust as a direct predictor (main effect) in government e-service adoption behavior [4][5][6][7][8][9]. Trust is also considered a moderator that may affect government e-service adoption behavior.…”
Section: Introductionmentioning
confidence: 99%
“…No levantamento dos principais estudos, os autores buscaram avaliar o valor público a partir da percepção dos cidadãos, em ambientes específicos, utilizando modelos, métodos e técnicas, como balanced scorecard, observação, pesquisa-ação longitudinal, aplicação de surveys e entrevistas. Apesar do crescente aumento de estudos internacionais na última década (Van der Wal, Nabatchi, & Graaf, 2015;Lopes, Luciano, & Macadar, 2018), pouco se tem estudado sobre criação de valor público no Brasil (Lopes, Luciano, & Macadar, 2018;Porto, 2018;Matos, Amaral, & Iquiapaza, 2018;Santos, Andrade, & Lima, 2019) e pouca atenção é dada às métricas (Meynhardt & Bartholomes, 2011;Williams & Shearer, 2011, Van der Wal, Nabatchi & Graaf, 2015Faulkner & Kaufman, 2018). A carência de desenvolvimento de métricas, para alguns autores, justifica-se pela falta de uma definição clara do que seja valor público (Alford & O'Flynn, 2009;Williams & Shearer, 2011;Faulkner, & Kaufman, 2018).…”
Section: Introductionunclassified